Resíduos de bananeira como substrato base para o cultivo in vitro de Coprinus comatus - Almeida, Laís Bentes de; Sales-Campos, Ceci; Carvalho, Cristiane Suely Melo de; Minhoni, Marli Teixeira de Almeida [UNESP]; Andrade, Meire Cristina Nogueira de (My University, 2013)
Coprinus comatus is an edible and lignolitic fungus which has presented great potential for commercial use due to its easy development in the different residues, such as banana tree leave. Thus, the mycelial growth of Coprinus comatus in culture media based on leaves of Thap-Maeo, Prata-Anã, Pelipita and Caipira banana tree cultivars, supplemented with 20% of wheat, soy and rice brans, was evaluated. 7 mm-wide discs of CCO 01/01 strain of C. comatus were inoculated in the middle of Petri dishes containing culture medium, inside a laminar flow chamber. Next, the dishes were arranged totally at random inside an incubator at 25 ºC. The daily measurements of the mycelial growth began after 24 hours, until one of the treatments reached the borders of the Petri dish. According to the results obtained, we verified that there was not effect of the kind of supplementation for culture media based on Thap-Maeo, Prata-Anã and Pelipita; the best growth averages for culture media based on Caipira were provided by wheat and rice brans. Therefore, banana residues may be a viable and ecologically correct choice for the cultivation of C. comatus, especially for Thap-Maeo and Prata Anã sorts, which provided the best growth averages, regardless of the supplementation used.

O Coprinus comatus é um fungo lignícola e comestível que tem demonstrado grande potencial para sua exploração comercial, por se desenvolver facilmente nos mais diferentes resíduos, entre eles a folha de bananeira. Assim, avaliou-se o crescimento micelial de Coprinus comatus em meios de cultura à base de folhas das diferentes cultivares de bananeira: Thap-Maeo, Prata-Anã Pelipita e Caipira, com 20% de suplementação com farelo de trigo, soja e arroz. Em câmara de fluxo laminar, discos de 7 mm de diâmetro, da linhagem CCO 01/01 de C. comatus, foram inoculados no centro das placas de Petri contendo meio de cultura. Em seguida, as placas foram dispostas inteiramente ao acaso em incubadora a 25 ºC. Após 24 horas, iniciaram-se as medições diárias do crescimento micelial, até que um dos tratamentos atingisse as bordas da placa de Petri. De acordo com os resultado obtidos, verificou-se que: para os meios de cultura à base das cultivares de bananeira Thap-Maeo, Prata-Anã e Pelipita não houve efeito do tipo de suplementação; para o meio à base da cultivar Caipira os farelos de trigo e arroz proporcionaram as melhores médias de crescimento. Assim, os resíduos de bananeira podem ser uma alternativa viável e ecologicamente correta no cultivo de C. comatus, especialmente as variedades Thap-Maeo e Prata-Anã que, independente da suplementação utilizada, proporcionaram as melhores médias de crescimento.
Banana tree residues as base substrate for the in vitro cultivation of Coprinus comatus
Keywords: Mushrooms; Residues; Mycelium; Cogumelos; Resíduos; Micélio